Literature Review: Gambaran Berbagai Skor Diagnosis Apendisitis dengan Skor Alvarado dalam Diagnosis Apendisitis Akut - Laily Alfisahrinie; Agung Ary Wibowo; Meitria Syahadatina Noor; Budianto Tedjowitono; Iwan Aflanie (Homeostasis, 2021)
Abstract: Appendicitis is an inflammation of the appendix vermiformis. Immediate surgery is the standard weakening to prevent perforation, but only by looking at clinical symptoms the negative appendectomy rate reaches 15-30%, leading to morbidity and even death. The ideal service system serves to speed up and improve diagnostic accuracy, the best known of which is the Alvarado score. Other service score tables are the King Isteri Pengiran Anak Saleha Appendicitis (RIPASA) score, Appendicitis Inflammatory Response (AIR) score, and Tzanakis score. The purpose of this literature review is to see an overview of the various appendicitis diagnosis scores with the Alvarado score in the diagnosis of acute appendicitis. The research method used a narrative literature review of 20 related literatures. Examining 11 literature discussing the Ripasa score, got superior in sensitivity and negative predictive rates. In 5 literature that discusses the Tzanakis score, it was found to be superior in sensitivity, positive and negative predictive numbers. And in 4 literature discussing AIR scores, it was found superior in specificity and positive predictive numbers. So that the use of scores other than Alvarado can be revoked in daily practice. Keywords: Appendicitis, Alvarado score, Ripasa score, Tzanakis score, AIR score. Abstrak: Apendisitis merupakan peradangan pada appendiks vermiformis. Pembedahan segera merupakan standar emas untuk mencegah terjadinya perforasi, tetapi hanya dengan melihat gejala klinis angka apendektomi negatif mencapai 15-30%, sehingga akan mengarah pada morbiditas dan bahkan kematian. Sistem penilaian yang ideal berfungsi untuk mempercepat dan meningkatkan akurasi diagnostik, yang paling dikenal adalah skor Alvarado. Terdapat skor penilaian lainnya yaitu skor Raja Isteri Pengiran Anak Saleha Appendicitis (RIPASA), skor Appendicitis Inflammatory Response (AIR), dan skor Tzanakis. Tujuan kajian literatur ini untuk melihat gambaran dari berbagai skor diagnosis apendisitis dengan skor Alvarado dalam diagnosis apendisitis akut. Metode penelitian menggunakan narrative literature review terhadap 20 literatur yang berkaitan. Terdapat 11 literatur yang membahas skor Ripasa, didapatkan unggul dalam sensitivitas dan angka prediksi negatif. Pada 5 literatur yang membahas skor Tzanakis, didapatkan unggul dalam sensitivitas, angka prediksi positif dan negatif. Dan pada 4 literatur yang membahas skor AIR, didapatkan unggul dalam spesifisitas dan angka prediksi positif. Sehingga penggunaan skor selain Alvarado dapat dipertimbangkan dalam praktek sehari-hari. Kata-kata kunci: Apendisitis, skor Alvarado, skor Ripasa, skor Tzanakis, skor AIR.